A CONCEPTUAL FRAMEWORK AND MATURITY MODEL TO APPRAISE COMPANIES FOR SMART MANUFACTURING - Onay, Seher/S (2020)
During the past decade, a fourth revolution has dominated the manufacturing industry within the production facilities as well as among the supply chain by utilizing today’s technologies. This new era introduced the smart manufacturing term to the world. As a result, fostering the conversion from traditional to smart manufacturing started. To survive during this transformation, companies need to understand its concept, requirements, and benefits. For this reason, this study aims to provide a comprehensive understanding of fundamental features and components of smart manufacturing, and a model that assesses companies' current status, capabilities, i.e. their maturity in this era. However, this transformation also brought fear to employees since it creates an image of unmanned production fields. Thus, a human transformation to “adapted people” is also required and assessed during smart manufacturing conversion.